Social representations of Salvadoran university students: validation of the Academic Self-Concept Scale (EAA) - Deleon Villagrán, Mauricio D. (2025)
This article aims to demonstrate the psychometric consistency of the Academic Self-Concept Scale (EAA) and to highlight its relationship with academic engagement and the performance of university students in El Salvador. It is a quantitative,  rosssectional,correlational study, with a stratified sampling by geographic subareas, with the participation of 506 students from a private university that covers the four zones of El Salvador during 2024. As part of the methodological design, the Academic Well-Being Scale (UWES-S) and an ad hoc questionnaire on the relevance given to teacher support were included in order to contrast the evaluated dimensions. The results indicated consistency and stability in the psychometric properties of the scales, as well as direct correlations and significant differences between dimensions of the instruments. It is concluded that academic self-concept directly influences student performance, since students’ self-perceptions are related to their academic dedication or engagement. These social representations impact their notion of achievement.